Islamic Attitude, Ethics, and Morality in Qur’anic Tafsir on Sustainability and Technology in Indonesia and Malaysia - Andri Nirwana; Mahmudulhassan; Zainora binti Daud (Solo International Collaboration and Publication of Social Sciences and Humanities, 2026)
Objective: This study aims to analyze the development, trends, and intellectual structure of Qur'anic exegesis (Tafsir) research in Indonesia and Malaysia through bibliometric analysis. It identifies influential scholars, journals, collaboration networks, and emerging research themes. Theoretical framework: The research is based on bibliometric analysis and knowledge mapping, using citation, co-authorship, and keyword co-occurrence analyses to examine the evolution and interdisciplinary development of Tafsir scholarship. Literature review: Previous studies have mainly focused on thematic and classical Tafsir, with limited bibliometric evidence. This study extends the literature by examining research productivity, collaboration, and emerging contemporary topics. Method: A quantitative bibliometric approach was employed using 273 Scopus-indexed publications selected from 1,056 records. Data were analyzed with R and Biblioshiny through citation, co-authorship, and keyword network analyses. Results: The findings indicate that Indonesia and Malaysia are the dominant contributors to Qur'anic exegesis research in Southeast Asia. Bibliometric mapping reveals influential scholars, productive journals, and expanding collaboration networks within the field. The analysis also identifies emerging research themes, including sustainability, environmental ethics, and digital technology, demonstrating a growing integration between traditional Tafsir studies and contemporary global issues. These results suggest that Qur'anic exegesis research is becoming increasingly interdisciplinary and responsive to societal challenges. Implications: The findings provide strategic insights for future Qur'anic studies, encouraging interdisciplinary collaboration and greater engagement with global challenges in Islamic scholarship. Novelty: This study presents a comprehensive bibliometric mapping of Tafsir research in Indonesia and Malaysia, offering a systematic overview of scholarly trends, collaboration patterns, and emerging interdisciplinary directions.